Behavior and design of nano/micro-scale carbon modified multifunctional cementitious composites. (3rd January 2022) - Pei, Chun; Wei, Liangliang; Qin, Zhaojun; Yu, Hongtao; Zhu, Ji-Hua; Xing, Feng
Graphical abstract: Highlights: Original self-made graphene dispersion with high concentration, high stability, and low price. Synergistic effect combined the advantages of graphene and carbon fiber. Effective design strategies proposed for nano/micro-scale carbon modified composites. Profitable, ecological, and promoting energy conservation and emission reduction. Abstract: This work proposes a design concept of nano/micro-scale carbon modified multifunctional cementitious composites based on the original fabrication method of combined graphene/PVA nanofluid additive, in which nano carbon material graphene was produced from low-cost graphite raw material and surface functionalized by PVA in water in a one-step preparation process, which can directly substitute water in the cement casting. Incorporating the complementary advantages of the bridging three-dimensional micron-scale carbon fiber and the pore-filling and lubricating two-dimensional nano-material graphene, the composite modification can not only improve the mechanical properties of cementitious composites but also gift them with high electrical conductivity, whose electrical resistivity dropped to 0.72 kΩ·cm compared to 13.12 kΩ·cm of the blank. In particular, under such low resistivity, the mechanical strengths were not reduced as with the addition of other single carbon materials but were improved compared with the blank. The results of this work provide a novel approach for designing and developing multifunctional cementitious composites, which would be a promising building material for structural health monitoring.